Blunted cardiovascular responses in individuals with type 2 diabetes and hypertension during cold and heat exposure - Rafieian, Mojdeh; Farbu, Erlend Hoftun; Höper, Anje Christina; Valtonen, Rasmus; Hyrkäs-Palmu, Henna; Perkiömäki, Juha; Crandall, Craig; Jaakkola, Jouni J. K.; Ikäheimo, Tiina Maria (Frontiers in Physiology, 2025)
IntroductionThe effect of type 2 diabetes (T2D) on indices of cardiovascular function during exposure to cold or hot environmental temperatures is not well known. Therefore, the aim of our study was to assess the effect of short-term whole-body cold and heat exposure on the cardiovascular responses in individuals with T2D.Material and methods10 participants with T2D and hypertension (mean age 64 ± 4 years) and 10 controls (mean age 63 ± 5 years) underwent 90 min of whole-body exposure to cold (10°C; 10% relative humidity) and heat (40°C; 50% relative humidity) in a randomized sequence on differing days. Central and brachial blood pressure (BP), heart rate (HR), and skin blood flow were measured before, during, and after the exposure.ResultsDuring cold exposure, subjects with T2D exhibited a smaller increase in central (14 (CI 95%:3, 23) vs. 43 (CI 95%:32, 53) mmHg, p < 0.05) and brachial systolic BP (12 (CI 95%:1, 22)) vs. 40 (CI 95%:30, 51) mmHg, p < 0.05) compared to controls. The corresponding reduction in HR in the cold was also less in T2D compared to controls (5 (CI 95%: 10, 0.02) vs. 9 (CI 95%: 14, −4) bpm, p < 0.05). Heat exposure reduced central and brachial BP similarly in both groups. However, the heat-related increase in HR was less pronounced in T2D subjects compared to controls (7 (CI 95%:1, 13) vs. 14 (CI 95%: 9, 19) bpm, p < 0.05). Finally, the magnitude of the increase in skin blood flow was less in the heat in T2D subjects (+210 (CI 95%: 41, 461) vs. +605 (CI 95%: 353, 855) PU, p < 0.05).DiscussionT2D attenuated cardiovascular responses, such as BP and HR during short-term exposure to cold, and HR and skin blood flow during short-term exposure to heat. These observations suggest impaired capacity to respond to environmental temperature extremes in individuals with T2D.